Foreign body in the bladder: A case report. (2017) - Shimokihara, Kota; Kawahara, Takashi; Hayashi, Yutaro; Tsutsumi, Sohgo; Takamoto, Daiji; Mochizuki, Taku; Hattori, Yusuke; Teranishi, Jun-ichi; Miyoshi, Yasuhide; Yumura, Yasushi; Yao, Masahiro; Uemura, Hiroji
Highlights: We experienced the foreign body had become severely calcified. The foreign bogy was successfully removed by bladder wall incision. The foreign body was covered by labor. Abstract: Foreign bodies are occasionally reported in the bladder. In most cases, the foreign body is removed via the transurethral approach. A 57-year-old male patient was referred to our hospital to undergo the retrieval of a foreign body from his bladder. However, the foreign body had become severely calcified and could not be removed transurethrally. Thus, an open bladder wall incision was necessary to remove it. We herein report a case of a foreign body in the bladder that had become calcified and which was successfully removed using a higher bladder incision approach. A careful preoperative examination should be performed to detect the characteristics of the foreign body and avoid the risk of bladder wall perforation.